Dog10K: an integrated Dog10K database summarizing canine multi-omics - Zhou, Tong; Pu, Shao-Yan; Zhang, Shao-Jie; Zhou, Qi-Jun; Zeng, Min; Lu, Jing-Sheng; Lu, Xuemei; Wang, Ya-Nan; Wang, Guo-Dong (Nucleic acids research, 2025)
The diversity observed in canine breed phenotypes, together with their risk for heritabily disorders of relevance to dogs and humans, makes the species an ideal subject for studies aimed at understanding the genetic basis of complex traits and human biomedical models. Dog10K is an ongoing international collaboration that aims to uncover the genetic basis of phenotypic diversity, disease, behavior, and domestication history of dogs. To best present and make the extensive data accessible and user friendly, we have established the Dog10K (http://dog10k.kiz.ac.cn/) database, a comprehensive-omics resource summarizing multiple types of data. This database integrates single nucleotide variants (SNVs) from 1987 canine genomes, de-novo mutations (DNMs) from 43 dog breeds with >40× sequence, RNA-seq data of 105057 single nuclei from hippocampus, 74067 single cells from leukocytes and 30 blood samples from published canid studies. We provide clear visualization, statistics, browse, searching, and downloading functions for all data. We have integrated three analysis tools, Selscan, LiftOver and AgeConversion, to aid researchers in custom exploration of the comprehensive-omics data. The Dog10K database will serve as a foundational platform for analyzing, presenting and utilizing canine multi-omics data.